Design and application of a multifunctional support for infusion (一种输液用多功能支架的设计与应用) - YANG Hui (杨慧); SUN Xiumei (孙秀梅) (Association of Integrative Nursing, 2024)
Medical infusion stand is an indispensable and frequently used medical device for clinical intravenous infusion. The rational use of its functions is an important link to ensure the smooth progress of treatment. This paper introduces a multi-functional support for infusion effectively, which avoids the problem of aisle congestion caused by the occupation of space by the blank storage frame or the problem of affecting the pedestrian movement, improves the safety of use, improves the work efficiency of nursing staff, and ensures the safety of medication to a certain extent. (医用输液架是临床静脉输液必不可少且使用最频繁的医疗器械, 其功能的合理使用是确保治疗顺利进行的重要环节。本研究介绍一种新型输液用多功能支架, 在一定程度上优化了置物框对空间的利用率, 有效提高了用药安全性和护理人员工作效率。)